The association between age at first calving and survival of first lactation heifers within dairy herds - Sherwin, V.E.; Hudson, C.D.; Henderson, A.; Green, Martin J. (Cambridge University Press, 2016)
The objective of this research was to evaluate the survival rate of primiparous heifers within a large sample of herds across the UK and specifically to assess the association between age at first calving (AFC) on their survival. Data from 437 herds was re-structured for analysis. Descriptive statistics were calculated, and a multilevel logistic regression model used to explore factors associated with the risk of first lactation culling. Potential explanatory variables included AFC, herd size, culling rate within the whole herd, calving season, herd mean 305d yield and herd mean calving interval. The mean within-herd culling rate for the primiparous heifers was 15.9%. The mean within-herd AFC was 29.6 months, with 35.9% of heifers having an AFC greater than 30 months of age. Multivariable analysis revealed a negative association between survival rate of primiparous heifers and increasing AFC, and also associations with herd culling rate in older cows and calving season. This study highlights the importance of AFC for survival of primiparous heifers, as well the need to address heifer wastage in herds with high culling rates.